Pengaruh Komitmen Organisasi Pemerintah Desa, Kompetensi Dan Peran internal audit terhadap keandalan pelaporan keuangan pemerintah desa dikabupaten halmahera utara - Yakub Rozani Gagali; Cris Kuntadi (Sekolah Pascasarjana Perbanas Jakarta, 2019)
This study aims to examine the effect of independent variables namely village government organizational commitment, competence, and the role of internal audit on the dependent variable, namely the reliability of village government financial reporting. This study uses a quantitative approach, using primary data through questionnaires. Respondents in this study were the village head, village secretary and village treasurer in the northern halmahera district. The population used as many as 594 village government budget management employees located in 198 villages in the administrative area of ​​North Halmahera Regency, the sample used was 82 respondents. Data were analyzed using multiple linear regression analysis and data testing carried out with the help of SPSS version 24. Based on the results of multiple linear regression analysis showed that part of the commitment of village government commitment, competence, and the role of internal audit had a significant influence on the reliability of village government financial reporting. The results of simultaneous testing of village government organizational commitment, competence, and the role of internal audit have a significant influence on the reliability of village government financial reporting. The coefficient of determination shows that village government organizational commitment, competence, and the role of internal audit are 64.1%, while the remaining 35.9% are influenced by other factors outside the research model.